2001
DOI: 10.1161/01.hyp.37.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Intrarenal Adrenomedullin and Its Receptor System in Heart Failure Rats

Abstract: Abstract-Calcitonin receptor-like receptor/receptor activity-modifying protein 2 (CRLR/RAMP2) and CRLR/RAMP3 complexes have been reported to be specific adrenomedullin (AM) receptors. In the present study, we evaluated the pathophysiological significance of renal AM and its receptor system in aortocaval shunt (ACS) rats. Renal AM levels were measured serially during 5 weeks after the operation. Renal gene expressions of AM, CRLR, RAMP2, and RAMP3 were measured at 2 weeks (decompensated phase) and 5 weeks (comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…A recent study reported that the mRNA levels of CRLR, RAMP2, and AM are increased in the atrium and ventricle in rats with heart failure (26). Another study showed that the expression of the AM receptor component gene is not altered in the kidney in rats with heart failure, despite the increase of AM gene expression (27). We also found that the expression levels of the AM, CRLR, RAMP2, and RAMP3 genes were increased in the hypertrophied heart induced by malignant hypertension (28).…”
Section: Cardiac Production Of Am In Heart Failuresupporting
confidence: 58%
“…A recent study reported that the mRNA levels of CRLR, RAMP2, and AM are increased in the atrium and ventricle in rats with heart failure (26). Another study showed that the expression of the AM receptor component gene is not altered in the kidney in rats with heart failure, despite the increase of AM gene expression (27). We also found that the expression levels of the AM, CRLR, RAMP2, and RAMP3 genes were increased in the hypertrophied heart induced by malignant hypertension (28).…”
Section: Cardiac Production Of Am In Heart Failuresupporting
confidence: 58%
“…Interestingly, there was a significant positive association between urine sodium excretion and renomedullary adrenomedullin levels (27). Jougasaki and colleagues, in their study on dogs with rapid ventricular pacing-induced heart failure, observed that adrenomedullin immunoreactivity appeared to be increased at various sites within the kidney (28).…”
Section: Cardiac Renal and Vascular Adrenomedullin In Heart Failurementioning
confidence: 99%
“…In regard to the kidney in heart failure, Yoshihara and colleagues reported that renal adrenomedullin levels were augmented in decompensated heart failure due to aortocaval shunts in rats, although RAMP 2 and RAMP 3 mRNA levels were not different between controls and heart failure animals (27). Interestingly, there was a significant positive association between urine sodium excretion and renomedullary adrenomedullin levels (27).…”
Section: Cardiac Renal and Vascular Adrenomedullin In Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Immediately after the heart was arrested by the injection of 2 mmol KCl, the left kidney was perfused with 30 mL of cold phosphatebuffered saline (pH 7.4) as previously reported and separated into the cortex and medulla, 12 frozen in liquid nitrogen, and stored at Ϫ80°C. The radioimmunoassay (RIA) for angiotensin II in renal cortical tissues was performed as reported previously.…”
Section: Measurement Of Angiotensin II Levels In Renal Cortexmentioning
confidence: 99%